Which perspectives for work in agriculture? Food for thought for a research agenda - Dedieu, Benoît; Nettle, Ruth; Schiavi, Sandra Mara de Alencar; Sraïri, Mohamed Taher; Malanski, Priscila Duarte (Frontiers in Sustainable Food Systems, 2022)
The 2nd International Symposium on Work in Agriculture (March 29–April 1 2021) was a moment for debate on the perspectives of work in agriculture. In this article, we propose to summarize the exchanges that outline the major issues from this event. We made a bibliometric analysis of all the contributions presented and a cross-cutting expert synthesis. Agricultural work and drivers of employment were the main topics of the presentations, with North and Global South countries facing different labor productivity dynamics. Some questions are continent specific: will OECD countries see agriculture without farmers? Will agriculture provide decent work to youth, notably in the Sub-Saharan Africa? With which models of agriculture? Some issues are common globally: the ability of the agroecological transition to improve working conditions and provide new jobs; the recognition of women and ethnic groups' contributions to work and to decisions. The digital revolution and the migration flows to and from rural areas and cities are also changing agricultural work substantially. Cross-cutting perspectives are introduced such as the potential of the decent work concept to foster the attractiveness of the agricultural professions, the effect of value chains and the potential of the territorial approach to work to foster interdisciplinary and transdisciplinary viewpoints in addressing problems in the domain.